O okolicznościach wyłączających podleganie ubezpieczeniom społecznym obywateli państw obcych na tle poglądów judykatury (art. 5 ust. 2 ustawy o systemie ubezpieczeń społecznych) - Stopka, Karolina (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The paper analyzes and assesses the views of the Supreme Court formulated in relation to Article 5 Section 2 of the Social Insurance System Act, which regulates the situations that exclude citizens of foreign countries from the scope of the Act. A broader assessment was made of the position of the Supreme Court according to which the provision of Article 5 Section 2 of the System Act excludes two groups of citizens of foreign countries from being subject to the Polish social insurance — firstly: foreigners whose stay in the territory of the Republic of Poland is not permanent, and secondly: citizens of foreign countries who are employed in the “diplomatic” posts mentioned therein. Also assessed were the views ascribing to the concept of “permanent character of stay” used in this provision a specific meaning in the context of social insurance, determined by the situation constituting the title to social insurance, as well as the view pointing to the need for dynamic interpretation of the phrase “not of permanent character”. The above views of the Supreme Court were assessed from the point of view of the normative meaning of the provision of Article 5 Section 2 for the legal regulation of the Act and expectations as to the wording and interpretation of the provisions determining the scope of the normative act. The assessment of these views also took into account the impact of the principle of personalism on the shaping of social security systems, the evolution of the social insurance legal regulation in this respect, as well as the manner in which the issue of social insurance was resolved in the Constitution of the Republicof Poland and the essence of insurance protection.
Keywords: social insurance; subject to social insurance; foreigner; jurisprudence